2008
DOI: 10.1016/j.biortech.2008.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Use of pulp mill inorganic wastes as alternative liming materials

Abstract: A laboratory aerobic incubation study was performed during 18 weeks under controlled conditions to assess the effects of applying different doses of pulp mill inorganic wastes on the physical-chemical properties of an acid Dystric Cambissol. Three different inorganic wastes were tested - wood ash, dregs and grits, and an agriculture limestone was used as reference. Results showed that increasing the dose applied of the different inorganic wastes tested always led to significant raises of soil pH at different i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
61
3
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 15 publications
9
61
3
3
Order By: Relevance
“…However, the standard deviations are not given for the pH and TOC values because the triplicate samples had exactly the same values. The pH of the grits was strongly alkaline (pH 13.1), and agrees with the findings of Cabral et al (2008), who reported pH values between 12.4 and 13.1 for slaker grits. The alkaline pH value and the existence of calcium carbonate, which is an active ingredient in agricultural lime, mean that the slaker grits have a liming effect and are therefore a potential soil conditioning or amendment agent.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…However, the standard deviations are not given for the pH and TOC values because the triplicate samples had exactly the same values. The pH of the grits was strongly alkaline (pH 13.1), and agrees with the findings of Cabral et al (2008), who reported pH values between 12.4 and 13.1 for slaker grits. The alkaline pH value and the existence of calcium carbonate, which is an active ingredient in agricultural lime, mean that the slaker grits have a liming effect and are therefore a potential soil conditioning or amendment agent.…”
Section: Resultssupporting
confidence: 90%
“…The agronomic benefits of the slaker grits as a nutrient source and a liming agent for acidic soils are well documented (Muse and Mitchell, 1995;Jordan et al, 2002;Cabral et al, 2008). As a consequence of the high calcium carbonate equivalents, the addition of grits raises the soil pH significantly, promoting neutralisation of soil acidity, which represents a valid and cost effective alternative to the use of commercial agricultural limestone (Castro et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The values are also lower than the ones found by Lacorte et al (2003) except for Cd, but higher than the ones reported by O'Brien et al (2003). Therefore, as also reported by Cabral et al (2008), metals do not seem to be a limiting factor for sludge application to land.…”
Section: Pulp Mill Sludge Characterizationcontrasting
confidence: 45%
“…O teor de K elevou-se de 190,00 para 260,21 mg dm -3 , teores considerados muito altos (CQFSRS/SC, 2016) (Tabela 1). Efeito similar foi obtido por Cabral et al (2008) na aplicação de cinza de biomassa florestal em solos com cultivo de plantas forrageiras.…”
Section: Resultado E Discussãounclassified